Optimization of Alpha-Amylase Production by a Local Bacillus paramycoides Isolate and Immobilization on Chitosan-Loaded Barium Ferrite Nanoparticles - Merehan Hallol; Omneya Helmy; Alla-Eldien Shawky; Ahmed El-Batal; Mohamed Ramadan (Fermentation, 2022)
We set out to isolate alpha-amylase producers from soil samples, optimize the production, and immobilize the enzyme on chitosan-loaded barium ferrite nanoparticles (CLBFNPs). Alpha-amylase producers were isolated on starch agar plates and confirmed by dinitrosalicylic acid assay. The potent isolate was identified by phenotypic methods, 16S-rRNA sequencing, and phylogenetic mapping. Sequential optimization of α-amylase production involved the use of Plackett–Burman (P–BD) and central composite designs (CCD), in addition to exposing the culture to different doses of gamma irradiation. Alpha-amylase was immobilized on CLBFNPs, and the nanocomposite was characterized by X-ray diffraction, Fourier-transform infrared spectroscopy, and scanning electron microscopy, with energy-dispersive analysis of X-ray analysis. Forty-five α-amylase producers were isolated from 100 soil samples. The highest activity (177.12 ± 6.12 U/mg) was detected in the MS009 isolate, which was identified as Bacillus paramycoides. The activity increased to 222.3 ± 5.07 U/mg when using the optimal culture conditions identified by P–BD and CCD, and to 319.45 ± 4.91 U/mg after exposing the culture to 6 kGy. Immobilization of α-amylase on CLBFNPs resulted in higher activity (246.85 ± 6.76 U/mg) compared to free α-amylase (222.254 ± 4.89 U/mg), in addition to retaining activity for up to five cycles of usage. Gamma irradiation improved α-amylase production, while immobilization on CLBFNPs enhanced activity, facilitated enzyme recovery, and enabled its repetitive use.